Kinetic validation of the LiMAx test during 10 000 intravenous 13C-methacetin breath tests. (28th November 2017) - Rubin, Tom Moses; Heyne, Karsten; Luchterhand, Axel; Jan Bednarsch,; W. R. Vondran, Florian; Polychronidis, Georgios; Malinowski, Maciej; Nikolic, Alen; Tautenhahn, Hans-Michael; Jara, Maximilian; Wünsch, Tilo; Stockmann, Martin; et al.
Abstract: The maximal liver function capacity (LiMAx) test, a novel 13 C-methacetin breath test, has proven clinical validity in determining hepatic metabolic capacity. In contrast to prior 13 C-methacetin breath test protocols, the LiMAx test is performed by intravenous body-weight-adjusted substrate administration. Furthermore, the DOB kinetics (delta over baseline of the time-dependent exhaled 13 CO2 / 12 CO2 ratio) are measured online at the bedside with a high time resolution in order to determine the maximum DOB. The aim of this study was to analyze the recorded DOB kinetics in a large population for further refinement of the test protocol. Two new methods of kinetic analysis are proposed in this article: the time dependency of the DOB kinetics and the time interval until half of the DOB maximum. A total of 10 100 LiMAx tests on 8483 patients performed during routine clinics at eight centers were available. The kinetic analysis revealed a specific pattern of DOB kinetics depending upon LiMAx result. In addition, potential co-factors for DOB kinetics, such as weight, height, gender and age, were analyzed, yielding a potential influence of gender and smoking behavior. Both the specific patterns and the proposed kinetic analysis have the potential to further improve the sensitivity and specificity of the test and its clinical applicability by shortening its duration.